"Capitalism Has a Conjunctural History but No Necessary Trajectory": A Comment on David Ruccio's Development and Globalization. Issue 4 (2nd October 2019) - Amariglio, Jack
Abstract : David Ruccio's book Development and Globalization is a watershed in how to write Marxian conjunctural history. Ruccio employs the notion and practice of conjunctural analysis through his use of concrete Marxian class analysis. His essays, written in the thirty-year period leading up to the 2007–8 Great Recession, are concerned with the problems of planning in transitional economies, of development and the abolition of capitalist class exploitation, and of globalization as a stand-in for imperialism. In each chapter, Ruccio resists the modernist Marxian urge to make all aspects of existing societies a manifestation of given "laws of motion" of capitalism. In its place, Ruccio's conjunctural analyses successfully open up the space for seeing and analyzing class, state, and other social processes and subjectivities that are multiple, hybrid, and heterogeneous.